Penerapan Urban farming untuk Peningkatan Ketahanan Pangan Rumah Tangga di Kampung Suryowijayan Yogyakarta - Umami, Arif; Anggrasari, Herdiana; Sustia Dewi, Ni Kadek Ema (JAST : Jurnal Aplikasi Sains dan Teknologi, 2025)
The Surya Makmur Farmers Group, formed in 2023 in Suryowijayan Village, Yogyakarta, consists of 20 housewives who were previously not economically productive. This urban farming program aims to increase household food security through training in modern agricultural technology such as vertical farming, tabulampot, organic fertilizers, and botanical pesticides. Demonstration plots (demplots) with smart plug-based drip irrigation were also developed to increase cultivation efficiency. This program has increased production by up to 50% in several commodities such as chilies, mustard greens, and corn. In addition, member empowerment has increased through institutional training and organic waste management. This program creates a sustainable impact on food security and community welfare.ABSTRAKKelompok Tani Surya Makmur, dibentuk pada tahun 2023 di Kampung Suryowijayan, Yogyakarta, beranggotakan 20 ibu rumah tangga yang sebelumnya tidak produktif secara ekonomi. Program urban farming ini bertujuan meningkatkan ketahanan pangan rumah tangga melalui pelatihan teknologi pertanian modern seperti vertikultur, tabulampot, pembuatan pupuk organik, dan pestisida nabati. Demonstration plot (demplot) dengan irigasi tetes berbasis smart plug juga dikembangkan untuk meningkatkan efisiensi budidaya. Program ini berhasil meningkatkan produksi hingga 50% pada beberapa komoditas seperti cabai, sawi, dan jagung. Selain itu, keberdayaan anggota meningkat melalui pelatihan kelembagaan dan pengelolaan limbah organic. Program ini menciptakan dampak berkelanjutan terhadap ketahanan pangan dan kesejahteraan masyarakat.